Grammaticalization as emergence of functional domains: three cases in Chadic - Zygmunt Frajzyngier (Studies in African Languages and Cultures, 2010)
The purpose of this article is to describe the grammaticalization of selected functions in Chadic languages[1], functions that have seldom been observed in other languages and that have been largely ignored by literature making theoretical claims but that have profound effects on the structures of languages involved. The selected grammaticalizations are important for the overall typologies of syntax and semantics. The selected grammaticalizations are: grammaticalization of non-categorial morphology whose function is to code the syntactic organization of the clause, i.e. the internal structure of the utterance; the coding of the category ‘goal’; and the coding of the domain of locative predication. Interestingly, the first and third grammaticalizations described here do not involve changes from a lexical item to a grammatical morpheme. The grammaticalization of non-categorial morphology has exploited phonological reduction to code one function and has exploited the most frequently used form in the coda of lexical items to code another function. The second grammaticalization, that of the category ‘goal’, may have a lexical item as its source. In addition to different sources, it appears that each grammaticalization had different motivations.